Invariant Solutions for Nonhomogeneous Discrete Diffusion Equation - M. N. Qureshi; A. Q. Khan; M. Ayub; Q. Din (Discrete Dynamics in Nature and Society)
One-dimensional optimal systems for nonhomogeneous discrete heat equation with different source terms are calculated. By utilizing these optimal systems invariant solutions are found. Also generating solutions are calculated, using the elements of the symmetry algebra.